Scope of Visum Et Repertum as a Legal Mean of Proof in Crime Related to Human Body in Rumah Sakit Bhayangkara Semarang - Trisnadi, Setyo (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Visum et repertum (VER) is part of forensic and medico-legal science. VER is a written report by a sworn doctor and has the authority of what he/shehas seen and and found in the evidence presented and conclude the evaluation for the trial process in the investigation to decide the suspect, for the basis ofprosecution, prove that an accused person is guilty, at the level of investigation, the request of VER is the authority of investigator of POLRI (The IndonesianNational Police). VER is prepared by a doctor with a special expertise under oath or medical professional and legal responsibilities and liabilities. Therehas been dualism concerning to the evidence of expert witness. First, an expert witness provides a sworn testimony in the trial as it is explicitly mentionedin article 184 of KUHAP (Code of Criminal Procedure). Second, VER is part of legal means of proof of expert testimony given by a legal medical doctoras stated in 184 KUHAP. The expert testimony in form of VER can be legal means of proof which can be used before the court. It is, however, not alwaysnecessary for prosecutor to use it for the adjudicating criminal case. However, criminal case related to human body, it was found that the prosecutorsmake the judgment based on the VER. The autopsy data of RS Bhayangkara in January to October 2012 showed that there were more male victim (58)compared to female victim (51) .The most common cause of death was persecution (91 ). The most common wound was bruise.